Does Compost Selection Impact Green Roof Substrate Performance? Measuring Physical Properties, Plant Development, and Runoff Water Quality. Issue 4 (2nd October 2017) - Matlock, Jason M.; Rowe, D. Bradley
ABSTRACT: Six green roof substrate blends were created by using composts sourced from local suppliers and the Michigan State University Student Organic Farm. Bulk density, field capacity, total porosity, and saturated hydraulic conductivity were determined for each substrate and compared to an un-amended expanded shale aggregate. Significant differences were detected in all measured physical properties. A plant growth study was conducted in a greenhouse. Ocimum basilicum (basil), Sedum floriforum (sedum), and Carex eburnea (bristleleaf sedge) were grown in a depth of 10 cm of all six substrates for 6 months. The greatest dry shoot masses in bristleleaf sedge and sedum were twice those of the smallest masses. The largest wet harvest of basil was four times greater than the smallest harvest. Runoff water was collected after simulated precipitation events on regular intervals during the plant growth study and analyzed for nitrate and phosphate concentrations. Ion concentrations were greatest on the first measurement date and decreased rapidly with time. Compost selection had a strong impact on initial nitrate and phosphate concentrations, but the influence of compost on concentrations diminished with time. Overall, compost selection was found to have measureable and meaningful impacts on green roof substrate performance.